Pemanfaatan Simbol Dalam Pembelajaran Matematika: Studi Dokumentasi Tentang Pemahaman Pelajar SMA Terhadap Konsep Abstrak - Renanda, Renanda; Sudiansyah, Sudiansyah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The use of symbols in mathematics learning is an essential element that helps students understand the abstract concepts that are the basis of modern mathematics. This study aims to analyze high school students' understanding of mathematical symbols, particularly in relation to abstract concepts, and provide strategic recommendations to improve the quality of learning. The method used is descriptive qualitative with a documentation study approach, involving data from test results, learning notes, and student assignments. Observation of the learning process and in-depth interviews with students and teachers were conducted to complement the data. The research population included high school students in Ketapang Regency, with a purposive sample of 90 students from three schools that have different characteristics, as well as mathematics teachers as additional informants. The results showed that students had a good understanding of basic symbols such as +, -, ×, ÷, and =. However, complex symbols such as ∑, √, π, and ∞, as well as abstract symbols such as x, y, and function (f(x)), are still a challenge. The results show that students have a good understanding of basic symbols such as +, -, ×, ÷, and =. However, complex symbols such as ∑, √, π, and ∞, as well as abstract symbols such as x, y, and function (f(x)), are still a challenge. The main factors influencing these results are the lack of intensive practice, limited interactive learning media, and lack of technological support. Visualization, interactive discussion and technology-based learning strategies proved more effective than the conventional lecture method. This study concludes that diversifying teaching methods, increasing access to interactive learning media and teacher training are strategic steps to improve students' understanding of mathematical symbols. Context-based approaches and varied analytical exercises are recommended to help students master mathematical symbols at a deeper level. This research makes a significant contribution to improving the quality of mathematics learning at the high school level.